Durability properties of recycled aggregate concrete - Jong, Ho Sing. (Universiti Malaysia Sarawak (UNIMAS), 2010)
In recent years, there are many studies been done on the recycled aggregate obtained from demolished concrete structures. Recycled aggregate concrete produced from recycled aggregate that obtained from demolished concrete structures has been studied and explored by the researches and engineers. The durability of the concrete is one of the most important factors to be considered in the design of new structures and when assessing the condition of existing structures. Construction of concrete is becoming increasingly complex and the importance of producing structures that are both cost effective and durable is highly emphasized during the construction process. An understanding of concrete durability is fundamental as it is the basis that constructs the service life of new or existing structures. The objective of this research is to perform an experimental study to compare the durability properties of Natural Aggregate concrete (NAC) and recycled aggregate concrete (RAC). This includes comparison between the fresh and hardened properties of RAC with the NAC.